Cell-like P systems with evolutional symport/antiport rules and membrane creation - Song, Bosheng; Li, Kenli; Orellana-Martín, David; Valencia-Cabrera, Luis; Pérez-Jiménez, Mario J. (Information and computation, 2020)
Cell-like P systems with symport/antiport rules are computing models inspired by the conservation law, in the sense that they compute by changing the places of objects with respect to the membranes, and not by changing the objects themselves. In this work, a variant of these kinds of membrane systems, called cell-like P systems with evolutional symport/antiport rules, where objects can evolve in the execution of such rules, is introduced. Besides, inspired by the autopoiesis process (ability of a system to maintain itself), membrane creation rules are considered as an efficient mechanism to provide an exponential workspace in terms of membranes. The presumed efficiency of these computing models (ability to solve computationally hard problems in polynomial time and uniform way) is explored. Specifically, an efficient solution to the SAT problem is provided by means of a family of recognizer cell-like P systems with evolutional symport/antiport rules and membrane creation which make use of communication rules involving a restricted number of objects.